2018
DOI: 10.26444/aaem/92350
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein (HDL) cholesterol – more complicated than we think?

Abstract: In the light of presented findings it seems that there is a need to seek a better diagnostic marker than HDL-C level. This study presents some possible directions for future research to bring us closer to the full understanding of the HDL particle and its role in patients with ischemic heart disease and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 90 publications
(110 reference statements)
0
10
0
4
Order By: Relevance
“…However, patients without CVD at baseline in the lower HDL tertile showed a slightly increased risk for all-cause mortality, thus confirming the well-known negative role of low HDL cholesterol serum concentration in individuals in primary prevention [30]. The effectiveness of HDL cholesterol quantity as a trustworthy marker for CV protection has been recently questioned [2]. Mutant ApoA-I Milano is a paradigmatic example of this incongruence: carriers of this mutation display very low levels of HDL cholesterol and are markedly protected from CVD [31].…”
Section: All-cause and Specific-cause Mortalitymentioning
confidence: 71%
See 2 more Smart Citations
“…However, patients without CVD at baseline in the lower HDL tertile showed a slightly increased risk for all-cause mortality, thus confirming the well-known negative role of low HDL cholesterol serum concentration in individuals in primary prevention [30]. The effectiveness of HDL cholesterol quantity as a trustworthy marker for CV protection has been recently questioned [2]. Mutant ApoA-I Milano is a paradigmatic example of this incongruence: carriers of this mutation display very low levels of HDL cholesterol and are markedly protected from CVD [31].…”
Section: All-cause and Specific-cause Mortalitymentioning
confidence: 71%
“…The high heterogeneity of HDL subspecies accounts for their different capabilities in reverse cholesterol transport and in atheroprotection [34,35]. In the presence of chronic subclinical inflammation, such as in coronary artery disease, impaired HDL vesselprotecting functions have been reported even without alteration in HDL cholesterol blood concentrations, which may remain in the normal range [2,4,5,7]. Similarly, in T2DM patients, characterized by chronic subclinical inflammation status and by the aforementioned atherogenic dyslipidemia, reaching normal or even high HDL cholesterol levels might not be effective in conferring atheroprotection [4,13].…”
Section: All-cause and Specific-cause Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Under pathological conditions, abnormal HDLs are not simply related to the overall amount of HDL-c herein contained, but their status is a direct consequence of their overall composition. Therefore, the quality of the HDL-c appears to be a better biomarker than the quantity of HDLs [5,46,59,60]. This evidence has increased interest in studying the dysfunctional HDLs in pathological conditions characterized by systemic inflammation and oxidative stress such as obesity, T2DM, and CVD [2,5,59,61,62].…”
Section: Dysfunctional Hdls: From Quantity To Qualitymentioning
confidence: 99%
“…In liver, HDL-C particles release lipid cargo and then lipid-poor HDL particles return to the circulation in order to repeat the cycle [15,16]. Experimental studies have demonstrated that under normal conditions HDL possesses antiatherogenic properties [15,27,28]. According to studies, HDL stimulates macrophage reverse cholesterol transport, which involves the extraction of excess cholesterol from lipid-laden macrophage foam cells present in the atherosclerotic plaque, the efflux of free cholesterol to mature HDL-C or extracellular lipid-poor apoA-I, and its transport to the liver for excretion in the bile [16,29].…”
Section: Hdl Role and Functionsmentioning
confidence: 99%